Crystallization and preliminary X‐ray diffraction analysis of three recombinant mutants of Vaccinia virus uracil DNA glycosylase. Issue 3 (24th March 2013) - Sartmatova, Darika; Nash, Taishayla; Schormann, Norbert; Nuth, Manunya; Ricciardi, Robert; Banerjee, Surajit; Chattopadhyay, Debasish
<x xml:space="preserve">Abstract</x> Amino‐acid residues located at a highly flexible area in the uracil DNA glycosylase of Vaccinia virus were mutated. In the crystal structure of wild‐type D4 these residues lie at the dimer interface. Specifically, three mutants were generated: (i) residue Arg167 was replaced with an alanine (R167AD4), (ii) residues Glu171, Ser172 and Pro173 were substituted with three glycine residues (3GD4) and (iii) residues Glu171 and Ser172 were deleted (Δ171‐172D4). Mutant proteins were expressed, purified and crystallized in order to investigate the effects of these mutations on the structure of the protein.